The thermophysical properties and the stability of nanofluids containing carboxyl-functionalized graphene nano-platelets and multi-walled carbon nanotubes - Karami, Hadi; Papari-Zare, Solmaz; Shanbedi, Mehdi; Eshghi, Hossein; Dashtbozorg, Amirhosein; Akbari, Amir; Mohammadian, Erfan; Heidari, Milad; Sahin, Ahmet Z.; Chew, Bee Teng (Elsevier, 2019)
Two structures of carbon-based materials with sp2-hybridized are carbon nanotubes and graphene arrayed in the concentric tube and two-dimensional sheet, respectively. The most important problems of graphene and carbon nanotube for use in various applications are insufficient dispersibility and their inadequate stability in different organic and aqueous solvents. The low interaction with other materials is second category problems of carbon nanostructures. Functionalization, a common method suggested by numerous researchers, can be employed to enhance this property. In this regard, the nanofluids containing graphene nanoplatelets and carboxylated multi-walled carbon nanotube were synthesized and dispersed in deionized water to prepare homogeneous samples of 0.1 and 0.2 wt%. The stability dependency of samples was investigated, for the first time, on ultrasonic time and microwave irradiation. Thermophysical properties including shear stress, viscosity, surface tension, density and stability were also measured and reported. © 2019 Elsevier Ltd